2011
DOI: 10.1113/jphysiol.2010.194241
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin down‐regulates proximal renal tubular reabsorption and causes a fall in glomerular filtration rate in humans

Abstract: Non-technical summary Recombinant human erythropoietin (rHuEPO) decreases circulating levels of renin and aldosterone, two hormones regulating water and salt homeostasis, but the effect of rHuEPO on renal function is unknown. This study demonstrates that rHuEPO reduces the reabsorption of water and sodium in the proximal renal tubules and, probably by activation of the tubuloglomerular feedback mechanism, also causes a fall in glomerular filtration rate. Thus, the decrease in plasma concentrations of renin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
41
2
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 38 publications
4
41
2
2
Order By: Relevance
“…Plasma clearance of infused insulin is mainly renal, as opposed to endogenous insulin, which to a major extent is subjected to a first-pass metabolism in the liver, and occurs by both glomerular filtration and proximal tubular reabsorption and degradation (11). Prolonged treatment with rHuEpo decreases proximal tubular reabsorption and glomerular filtration rate (42). This could explain the slower clearance of insulin during the clamp in the ESA-treated subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Plasma clearance of infused insulin is mainly renal, as opposed to endogenous insulin, which to a major extent is subjected to a first-pass metabolism in the liver, and occurs by both glomerular filtration and proximal tubular reabsorption and degradation (11). Prolonged treatment with rHuEpo decreases proximal tubular reabsorption and glomerular filtration rate (42). This could explain the slower clearance of insulin during the clamp in the ESA-treated subjects.…”
Section: Discussionmentioning
confidence: 97%
“…The enhanced Hct value in rats might be due to a more sensitive hypoxia-sensing system in the kidneys, which could include stabilization of the hypoxic inducible factor (HIF), expression of HIF regulatory proteins and/or synthesis of erythropoietin (Epo) (Franke et al, 2013). In addition, it is worth mentioning that the synthesis of Epo in the kidney is regulated by the glomerular filtration rate (Olsen et al, 2011) because the consumption of O 2 in the kidneys (a major determinant of local P O2 ) is tightly dependent on sodium reabsorption and glomerular filtration rate (Donnelly, 2001). Accordingly, a lower glomerular filtration rate and/or sodium reabsorption in mice compared with rats could contribute to lower Epo production and reduced Hct.…”
Section: Discussionmentioning
confidence: 99%
“…Applying recombinant human erythropoietin in the treatment of these patients reduce the complications of anemia in such patients (8). In the present study, it was indicated that CKD patients' GFR was 76.95±5.97 before the prescription of erythropoietin.…”
Section: Discussionmentioning
confidence: 63%